Unsaturated Soil Water Retention Characteristics, Electrical Conductivity and Compressibility of a Poorly Graded Fujian Soil Amended with Biochar - Liu, Allen; Garg, Ankit; Yanning, Wang; Kamchoom, Viroon; Zhussupbekov, Askar (My University, 2026)
This study investigates the effect of peach shell biochar on the unsaturated soil water retention characteristics, electrical conductivity (EC), and its correlation with the compressibility of poorly graded Fujian soil, thereby addressing a critical gap in biochar research for geotechnical applications. The study aims to explore an economical approach to accessing geotechnical properties using EC. Biochar (produced at 600 °C) was mixed with sand at 0%, 5%, and 10% ratios and tested using a modified oedometer for simultaneous EC and compressibility measurements. Results reveal that 10% biochar increased EC by 354 mS/m under 200 kPa stress, a fourfold enhancement over 5% biochar (88 mS/m), attributed to conductive pathways formed by biochar particles under compression. Soil settlement decreased by 17% (0.282ΔH) and 21% (0.268ΔH) at 5% and 10% biochar, respectively, compared to bare sand (0.340ΔH). The air-entry value surged from 0.40 kPa (bare sand) to 0.71 kPa (5% biochar) and 1.41 kPa (10% biochar), enhancing moisture retention by 78% and 253%. The EC-void ratio relationship diverged markedly: bare sand showed a declining EC with reduced void ratio (0.112 Δe), while biochar-amended soils exhibited a rising EC (Δe = 0.056 for 5% and 0.036 for 10%) due to particle conduction dominating over pore-water losses. These findings offer feasible geotechnical applications: the stress-responsive EC enables real-time stability monitoring in embankments or landfill covers via non-invasive resistivity tomography, while reduced compressibility positions biochar-amended sand as a sustainable alternative for foundations in flood-prone or arid regions. Enhanced air-entry values further mitigate drought-induced cracking and erosion. The dual role of biochar, improving conductivity and mechanical stability, supports its integration into green infrastructure strategies.
Keywords: Biochar; Biochar monitoring; Electrical conductivity; Green infrastructure; Hygroscopicity